The Effect of Box Jump Exercise on Increasing Leg Muscle Explosive Power in Volleyball Players at SMA N 10 Makassar - Hasanuddin, Muh. Sawqi; Hasanuddin, M Iqbal; Hasanuddin, M. Imran; Hasanuddin, M. Irfan (Department of Physical Education, Sport, Health and Recreation, 2023)
Good volleyball players need the support of good physical abilities. Explosive leg muscle power is necessary for the implementation of starting and repulsing at certain angles, where strength is the basic muscle of power and muscle explosive power. Based on this, strength is the main element to produce power and muscle endurance. Muscle power can be increased and developed through box jump exercise. This research is a pre-experimental research that aims to determine the effect of box jump excercise on increasing leg muscle explosive power in volleyball players with a one group pretest-posttest research design. The sampling technique was purposive sampling so that a total sample of 10 people was obtained. The results show that the average value of the increase in leg muscle explosive power before treatment was carried out with a mean value of 57.90. As for the average after treatment with a value of 64.20. The results of the Wilcoxon test show that giving box jump training could increase the explosive power value of the leg muscles. The conclusion of this study is that giving box jump training for 8 treatments can increase the explosive power value of the leg muscles with a value of p = 0.005, which means p <a0.05 so that it can be concluded that there is an effect of giving box jump excercise on increasing jumping power in volleyball players